Transgressive Little Pests: Hiker Descriptions of "Shelter Mice" on the Appalachian Trail. (2nd January 2019) - Marx, Kate
ABSTRACT: Running between Springer Mountain in the state of Georgia, and Mount Katahdin in Maine, the Appalachian Trail (AT) is a more than 2, 000 mile long "wilderness" corridor in the United States. People aiming to undertake a trek of the entire length of the trail can expect to spend approximately six months of their lives on it, sleeping outdoors or in the rudimentary, three-sided shelters that are dotted along it. This paper looks at hiker narratives that described unpleasant encounters between themselves and the mice ( Mus musculus and Peromyscus maniculatus ) who inhabit these shelters. Many people who attempt to hike the entire length of the AT also choose to blog about their experiences on the trail, thereby creating a parallel community online of AT "thru hikers" as they are known. The data for this study were retrieved from blogs posted by AT thru hikers over the years 2015 and 2016. The most common response to shelter mice was one expressing deep discomfort. This paper asks what it was like to live in close proximity to a species that people usually avoid, what about mice meant that they were perceived as distasteful and even disgusting, and how hikers thought about these nonhuman animals and made sense of their encounters with them afterwards. It is found that hiker reactions to shelter mice were informed largely by their perception of them as being transgressive.